Intelligent Optimization of Modulation Indexes in Unified Tracking and Communication System. (January 2016) - Yang, Wei-wei; Cong, Bo; Huang, Qiong; Zhu, Li-wei
Abstract: In the unified tracking and communication system, the ranging signal and the telemetry, communication signals are used in the same channel. In the link budget, it is necessary to allocate the power reasonably, so as to ensure the performance of system and reduce the cost. In this paper, the nonlinear optimization problem is studied using intelligent optimization method. Simulation analysis results show that the proposed method is effective.